Estado, educação e modernização agrária: o papel da Escola de Engenharia de Porto Alegre(RS:1889/1930) - Alves, Leonice Aparecida de Fátima (Universidade do Vale do Rio do Sinos, 2008)
The present work analyzed the implementation of the proposed agrarian modernization by the ruralism in the education aspect, focusing the agronomic education subsidized by the State Government, during the Old Republic, which it had at the Porto Alegre Engineering School its main agent. We should except that the themes regarding other aspects of the agrarian modernization tangentially were contemplated serving as reference for the composition of a wide prospect concerning the form that assumed the ruralism implementation in Rio Grande do Sul. The study was developed based from data picked in the theoretical production regarding agrarian and education matter, as well as a detailed analysis of documents of the government of Rio Grande do Sul, of the legislation that regulated the matter and of the documentation of the Porto Alegre Engineering School. In this work it was evident the existence of a project proposed by the State to modernize the field and to consolidate the capitalism in Rio Grande do Sul, assuming
Keywords: modernização agrária; República Velha; Rio Grande do Sul; ruralismo; educação agronômica; agrarian modernization; Old Republic; ruralism; agronomic education; Ciências Humanas